Iranian entrepreneurship : deciphering the entrepreneurial ecosystem in Iran and in the Iranian Diaspora - Rezaei, Shahamak; Dana, Leo Paul; Ramadani, Veland (Springer, 2017)
This book presents a comprehensive, state-of-the-art portrait of entrepreneurship and small business management issues in Iran, and among the Iranian Diaspora. The major contributions in this book address topics such as innovation, female entrepreneurship, social entrepreneurship, migrant entrepreneurship, corporate entrepreneurship, institutional support of entrepreneurial initiatives and more. This book is the outcome of an extensive research endeavor spanning several years and includes the latest contributions from highly respected authors and experts from Iran and beyond.